Implementasi Asas Kelangsungan Usaha (Going Concern) terhadap Notaris Pailit - Baiq Imanul Hamdi; Siti Anisah (International Forum of Researchers and Lecturers, 2025)
The legal mechanism of bankruptcy relies on the concept of debt, because the absence of debt undermines the fundamental purpose of bankruptcy as a legal institution to liquidate the debtor's assets to satisfy creditors' claims. Debt is the main criterion that must be met in order to be able to apply for bankruptcy, along with additional provisions such as having two or more creditors, as stipulated in Article 2, paragraph (1) of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (Bankruptcy Law). Notaries who have completed the bankruptcy process and are undergoing rehabilitation to improve their good name cannot re-apply to become Notaries. Here, the Notary will lose his/her right to work to carry out his/her position simply because the Notary has or has been sentenced to bankruptcy by the court. This bankruptcy is simply the notary's inability to pay the debt owed to the creditor, not a criminal act. If associated with the provisions contained in the 1945 Constitution of the Republic of Indonesia, namely Article 28 letter d concerning Human Rights which explains that everyone has the right to work and receive fair and proper compensation and treatment in employment relations, the efforts made in this problem are handled in accordance with the law and will be a substantial obligation for the curator. Based on Article 1 number 5 (Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations), it states that a curator is an individual or an estate office appointed by the court to resolve and manage all problems of the bankrupt debtor's assets under the supervision of a supervising judge based on applicable laws. The citation of the law shows the clear jurisdiction of the curator over the debtor's property and assets.